Detailed hydrodynamic and X-ray spectroscopic analysis of a laser-produced rapidly-expanding aluminium plasma - Chambers, D; Glenzer, S; Hawreliak, J; Wolfrum, E; Gouveia, A; Lee, R; Marjoribanks, R; Renner, O; Sondhauss, P; Topping, S; Young, P; Pinto, P; et al. (2001)
We present a detailed analysis of K-shell emission from laser-produced rapidly-expanding Al plasmas. This work forms part of a series of experiments performed at the Vulcan laser facility of the Rutherford Appleton Laboratory, UK. 1-D planar expansion was obtained by over-illuminating A1-microdot targets supported on CH plastic foils. The small size of the A1-plasma ensured high spatial and frequency resolution of the spectra, obtained with a single crystal spectrometer, two vertical dispersion variant double crystal spectrometers, and a vertical dispersion variant Johann Spectrometer. The hydrodynamic properties of the plasma were measured independently by spatially and temporally resolved Thomson scattering, utilizing a 4ω probe beam. This enabled sub- and super-critical densities to be probed relative to the 1ω heater beams. The deduced plasma hydrodynamic conditions are compared with those generated from the 1-D hydro-code Medusa, and the significant differences found in the electron temperature discussed. Synthetic spectra generated from the detailed term collisional radiative non-LTE atomic physics code Fly are compared with the experimental spectra for the measured hydrodynamic parameters, and for those taken from Medusa. Excellent agreement is only found for both the H- and He-like A1 series when careful account is taken of the temporal evolution of the electron temperature. © 2001 Published by Elsevier Science Ltd.